THE FORMATION AND DEVELOPMENT OF CRIMINAL REGISTRATION - Пашко, В. І. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article is devoted to the history and origin of criminal registration in the whole world andUkraine in particular. Analyzes the major historical milestones and scientific basis of criminal registration.The content of the first forensic classifications on the registration of objects and navo-ditsya list of scientists who have contributed to their further development.